Authentic Material Media to Enhance Students’ Reading Descriptive Text - Sri Rahayu Siregar; Zainuddin Zainuddin (English Education : English Journal for Teaching and Learning, 2021)
This research was aimed to find out the effect of using authentic material media on descriptive text reading comprehension at the XI grade MAS Baharuddin Tapanuli Selatan. Research methodology that used in this research was quantitative method. Types of the research was experimental research. The population of the research was the students at XI grade of MAS Baharuddin Tapanuli Selatan. Further, the sample of the research included 44 students. They were  experimental class consist of 25 students and control class consist of 19 students. In collecting the data, the researcher used test to know students’ descriptive text reading comprehension by learning using authentic material media. To analyze the data, the researcher used t-test formula. After using Authentic Material media the result of T-test  tcount was bigger than ttable (2.781.67). It means that hyphothesis alternative (Ha) was accepted. It was concluded that there was significant effect of using Authentic Material Media.